Microfiber insulation products for improved material efficiency
Patent Information
- Application Number
- JP2023572972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-04
- Filing Date
- 2022-06-03
- Publication Date
- 2025-04-08
AI Technical Summary
Existing fiberglass insulation products face challenges in achieving improved thermal performance and material efficiency when reducing fiber diameter below 4 microns, as this traditionally results in a negative impact on thermal insulation value and overall product weight.
The development of fiberglass insulation products with glass fibers having an average diameter ranging from 8 to 15 microns, coated with a cross-linked formaldehyde-free binder composition, and oriented to enhance thermal performance and material efficiency, achieving a material efficiency of at least 50R·ft²/lb with a thermal conductivity of 0.55 BTU-in/(hr·ft²·°F) or less.
The solution results in fiberglass insulation products with significantly improved thermal performance and material efficiency, demonstrating reduced thermal conductivity and lower product weight while maintaining or exceeding desired R-values, thus enhancing overall insulation effectiveness.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] FIELD OF THE INVENTION This application relates generally to fiberglass insulation products, and more particularly to fiberglass insulation products with improved performance characteristics.
[0002] [Citation of Related Applications] This application claims priority to and any benefit of U.S. Provisional Patent Application No. 63 / 196,895, filed June 4, 2021, which is incorporated by reference in its entirety. [Background technology]
[0003] The term "fibrous insulation product" encompasses a variety of compositions, articles of manufacture, and manufacturing processes. Mineral fibers, such as glass fibers, are commonly used in insulation products and nonwoven mats. Fiber insulation is typically produced by fiberizing a molten composition of polymer, glass, or other minerals and spinning the fibers from a fiberizer, such as a rotating spinner. To form the insulation product, the fibers produced by the rotating spinner are pulled downward from the spinner toward a conveyor by a blower. As the fibers move downward, a binder material is sprayed onto the fibers, and the fibers are collected on the conveyor in a high-loft, continuous blanket. The fiber-binder matrix provides the insulation product with resilience for post-packaging recovery, as well as stiffness and handleability, allowing the insulation product to be handled and applied as needed within a building's insulation cavity. The binder composition also protects the fibers from interfilament abrasion and promotes compatibility between the individual fibers.
[0004] The blanket containing the binder-coated fibers is then passed through a curing oven, and the binder is cured to set the blanket to a desired thickness. After the binder composition has cured, the fibrous insulation can be cut to length to form individual insulation products, and the insulation products can be packaged for shipment to a customer's location. One typical insulation product produced is an insulation batt or blanket, which is suitable for use as cavity or airspace (e.g., wall, floor, ceiling) insulation within a residence or other building, and may also be used to insulate attics or other areas within a building. Such insulation batts or blankets are typically relatively flexible or rollable, one-piece structures. Another common insulation product is air-blown or loose-pack insulation, which is suitable for use as sidewall and attic insulation within residential and commercial buildings and some hard-to-reach locations. Such loose-pack insulation is often formed as many relatively small, separate pieces, tufts, or the like, which may or may not be coated with a binder. Loose-fill insulation may also be formed in small cubes that are cut from the insulation blanket, compressed, and packaged in bags.
[0005] The insulating performance of an insulating material is primarily determined by the ratio of the thickness of the material divided by its thermal conductivity (k), which is the amount of heat that must be transferred through one square foot (0.0929 m) of insulation to raise or lower the temperature by one degree from one side of the insulation to the other. 2 ) the amount of heat (in BTUs per hour) that can be transmitted through a material. The greater the thickness and the lower the k value, the better the insulating performance of the material.
[0006] Fiber insulation for building products requires low thermal conductivity to be effective in wall and ceiling cavities. It is also desirable to reduce overall product weight, although reducing product weight generally negatively impacts thermal performance. Attempts have been made to reduce product weight, particularly by reducing the diameter of the fibers used to form the fiber insulation product; however, such fiber insulation products have traditionally had average fiber diameters of about 4 microns (1 micron is equal to 3.94 hundred-thousandths of an inch, or 3.94HT) or greater. Summary of the Invention [Problem to be solved by the invention]
[0007] However, such a reduction in fiber diameter has previously been found to negatively impact the insulation value (R-value) of a product at a particular areal weight and product thickness. Thus, it has previously been impractical to reduce the average fiber diameter of an insulation product below 4 microns because such products have been unable to meet performance requirements while still being economical. Accordingly, there has been a heretofore unmet need for insulation products made with fibers finer than 4 microns that can effectively meet necessary performance requirements, such as thermal performance, while still improving overall material efficiency. [Means for solving the problem]
[0008] Various aspects of the present concept relate to an insulation product with improved material efficiency, the insulation product comprising a plurality of glass fibers and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, the insulation product having a length, a width, and a thickness, the length being greater than each of the width and the thickness. The glass fibers have an average fiber diameter ranging from 8HT (2.03 μm) to 15HT (3.81 μm), including the range from 12HT (3.05 μm) to 14.5HT (3.68 μm). In this or other embodiments, the insulation product may have a binder content (LOI) of 8% or less by weight.
[0009] For any of the exemplary embodiments disclosed herein, at densities (x) between 0.2 pcf and 1.6 pcf, the insulating product has a viscosity of 100 MPa (100 psi) according to the following formula (VII): Formula (VII) y=40.1916068x 2 -120.5813540x+129.628397 For any of the exemplary embodiments disclosed herein, the insulation product may have a density (x) ranging from 0.5 pcf to 1.35 pcf, including from 0.7 pcf to 1.0 pcf.
[0010] For any of the exemplary embodiments disclosed herein, the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness, and at least 30% by weight of the glass fibers being oriented within ±15° of a plane parallel to the length of the insulation product.
[0011] In some exemplary embodiments, at least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product. In these or other embodiments, at least 40% by weight of the glass fibers are oriented within ±15° of a plane parallel to the length of the insulation product.
[0012] For any of the exemplary embodiments disclosed herein, prior to crosslinking, the formaldehyde-free binder composition comprises at least one monomeric polyol and polycarboxylic acid in a total amount of at least 45 wt.%, based on the total weight of the binder composition.
[0013] Another exemplary embodiment relates to a lightweight insulation product, the lightweight insulation product comprising a plurality of glass fibers having an average fiber diameter of less than 15HT (3.81 μm) and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, the insulation product having an R-value ranging from 19 to 24, an areal weight (W) of 0.3 lbs / sq ft to 0.5 lbs / sq ft, and a density of 0.7 lbs / cu ft to 1.0 lbs / cu ft. Additionally, the insulation product satisfies the following equation (2): Equation (2): ME=R value / W where ME is at least 28R·sq. ft / lb and W is the pounds of mass per square foot (lb / ft 2 ) is the product area weight expressed as
[0014] For any of the exemplary embodiments disclosed herein, the insulation product may have a material efficiency of at least 50 R·sq. ft / lb or at least 60 R·sq. ft / lb and a thickness (T1) of between 5.0 inches (12.7 cm) and 8.0 inches (20.32 cm).
[0015] In these or other embodiments, the insulation product may have a thermal conductivity k value of 0.55 BTU-in / (hr·ft 2 ·°F) or less.
[0016] For any of the exemplary embodiments disclosed herein, the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness, and at least 30% by weight of the glass fibers being oriented within ±15° of a plane parallel to the length and width of the insulation product.
[0017] For any of the exemplary embodiments, the insulation product has a density (x) between 0.2 pcf and 1.6 pcf, and the insulation product has a viscosity that satisfies the following formula (VI): Formula (VI) y=40.1916068x 2-120.5813540x+131.7360668 Achieve a material efficiency (y) that meets or exceeds the value (y) expressed in R·ft² / lb.
[0018] Yet another exemplary embodiment relates to a method for improving the material efficiency of an insulation product, the method including the steps of fiberizing molten glass into a plurality of glass fibers, coating the glass fibers with an aqueous formaldehyde-free binder composition, randomly depositing the glass fibers on a moving conveyor to form an uncured fiberglass blanket, and passing the uncured fiberglass blanket through a curing oven to crosslink the binder composition and form a fibrous insulation product, the insulation product having a length, a width, and a thickness, the length being greater than each of the width and the thickness.
[0019] The glass fibers have an average fiber diameter ranging from 8HT (2.03 μm) to 15HT (3.81 μm). For any of the exemplary embodiments, the insulation product may have a density (x) of 0.2 pcf to 1.6 pcf, and the insulation product may have a density (x) of 0.2 pcf to 1.6 pcf, and the insulation product may have a density (x) of 0.2 pcf to 1.6 pcf, and the density (x) of the insulation product may be determined according to the following formula (VII): Formula (VII) y=40.1916068x 2 -120.5813540x+129.628397 Formula (VI) y=40.1916068x 2 -120.5813540x+131.7360668 Achieve a material efficiency (y) that meets or exceeds the value (y) expressed in R·ft² / lb.
[0020] For any of the exemplary embodiments disclosed herein, the insulation product may have a density (x) in the range of 0.5 pcf to 1.35 pcf, including the range of 0.7 pcf to 1.0 pcf.
[0021] For any of the exemplary embodiments disclosed herein, the insulation product may have a material efficiency (y) of at least 55R·ft² / lb, an areal weight (W) of between 0.3 lb / ft² and 0.5 lb / ft², and a thickness (T1) of between 0.5 inches (1.27 cm) and 8.0 inches (20.32 cm).
[0022] The features and advantages of the present invention will become apparent to those skilled in the art to which the present invention pertains from the following description taken in conjunction with the accompanying drawings. [Brief explanation of the drawings]
[0023] [Figure 1] 1 is a perspective view of an exemplary embodiment of a fiber insulation product. [Figure 2] 2 is an elevational view of an exemplary embodiment of a manufacturing line for producing the fiber insulation product of FIG. 1. [Figure 3] FIG. 2 is a scanning electron microscope ("SEM") image showing a cross section of an exemplary fiber insulation product formed from glass fibers having an average fiber diameter of 14.5 HT. [Figure 4] FIG. 2 is an SEM image showing a cross section of an exemplary fiber insulation product formed from glass fibers having an average fiber diameter of 14.5 HT. [Figure 5] FIG. 1 is an SEM image showing a cross section of a conventional fiber insulation product made of glass fibers with an average fiber diameter of 16.7 HT and an insulation value of R-21. [Figure 6] FIG. 1 is a graphical representation of fiber orientation distribution within ±15° of a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fiber insulation product formed with glass fibers having an average fiber diameter of 14.5HT. [Figure 7] FIG. 1 is a graphical representation of fiber orientation distribution within ±30° of a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fiber insulation product formed with glass fibers having an average fiber diameter of 14.5HT. [Figure 8]FIG. 1 is a graphical representation of fiber orientation distribution within ±50° of a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fiber insulation product formed with glass fibers having an average fiber diameter of 14.5HT. [Figure 9(a)] FIG. 1 is a SEM image showing the fiber orientation of a 24 mm×16 mm cross section of an exemplary microfiber insulation product formed from glass fibers having an average fiber diameter of about 14HT. [Figure 9(b)] 9(b) is a graphical representation of a fiber orientation distribution curve (measured in degrees, based on a plane parallel to the product length L1 (0°)) taken at a cross section along the machine direction of the fibrous insulation product of FIG. 9(a). [Figure 10(a)] FIG. 1 is a SEM image showing the fiber orientation of a 24 mm×16 mm cross section of an exemplary microfiber insulation product formed from glass fibers having an average fiber diameter of about 14HT. [Figure 10(b)] 10(b) is a graphical representation of a fiber orientation distribution curve (measured in degrees, based on a plane parallel to the product length L1 (0°)) taken at a cross section along the machine direction of the fibrous insulation product of FIG. 10(a). [Figures 11(a)-11(c)] 11(a)-11(c) are SEM images showing the parallel fiber bundles present in an exemplary fiber insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figures 12(a)-12(c)] 12(a)-12(c) are SEM images showing the parallel fiber bundles present in an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 13(a)-13(b)] 13(a) and 13(b) are SEM images showing binder gussets present in an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 14] FIG. 1 is a graphical representation of a predicted thermal conductivity (k-value) curve per product density compared to an actual thermal conductivity (k-value) curve per product density. [Figure 15] FIG. 1 is a graphical illustration of a predicted material efficiency curve per product density compared to an actual material efficiency curve per product density. [Figure 16]FIG. 1 is a graphical representation of a predicted material efficiency curve per product density compared to an adjusted material efficiency curve per product density. DETAILED DESCRIPTION OF THE INVENTION
[0024] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terms used in the description herein are for the purpose of describing exemplary embodiments only and are not intended to be limiting of the exemplary embodiments. Thus, the general inventive concept is not limited to the specific embodiments described herein. Although other methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, the preferred methods and materials are described herein.
[0025] As used in the specification and claims, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly dictates otherwise.
[0026] Unless otherwise specified, all numerical values expressing size ranges, e.g., amounts of ingredients, properties such as molecular weight, reaction conditions, and physical and measured properties, and other numerical values used in the specification and claims should be understood in all instances to be modified by the term "about." Accordingly, unless specified to the contrary, the numerical properties set forth in the specification and claims are approximations that may vary depending upon the desired properties sought to be obtained in the embodiments herein. At the very least, each numerical parameter should be construed in light of significant digits and ordinary rounding approaches.
[0027] Unless otherwise specified, any element, any property, any feature, or combination of elements, properties, and features can be used in any embodiment disclosed herein, regardless of whether the element, property, feature, or combination of elements, properties, and features is explicitly disclosed in an embodiment. As will be readily understood, features described in connection with any particular aspect described herein can be utilized with other features described herein, provided such features are compatible with that aspect. In particular, features described herein in connection with a method can be utilized with a textile product, and vice versa; features described herein in connection with a method can be utilized with an aqueous binder composition, and vice versa; and features described herein in connection with a textile product can be utilized with an aqueous binder composition, and vice versa.
[0028] Notwithstanding that the numerical ranges and parameters setting forth the illustrative embodiments are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Every numerical range given throughout this specification and the claims will include every narrower numerical range that falls within such broader numerical range, as if such narrower numerical ranges were all expressly written herein.
[0029] As used herein, the terms "binder composition," "aqueous binder composition," "binder formulation," "binder," and "binder system" can be used interchangeably and are synonymous. Additionally, as used herein, the terms "formaldehyde-free" and "no added formaldehyde" can be used interchangeably and are synonymous.
[0030] All ranges are understood to include all possible subranges within the outer boundaries of that range. Thus, for example, a density range of 0.2 pcf to 2.0 pcf discloses, for example, 0.5 pcf to 1.2 pcf, 0.7 pcf to 1.0 pcf, etc.
[0031] The term "substantially free" means that the composition contains less than 1.0% by weight of the listed component, including amounts of 0.8% by weight or less, 0.6% by weight or less, 0.4% by weight or less, 0.2% by weight or less, 0.1% by weight or less, 0.5% by weight or less, and 0.01% by weight or less.
[0032] As used herein, the unit "pound" or "lb" refers to pounds-mass (where 1 pound equals 453.6 g).
[0033] The present disclosure relates to fiberglass insulation products formed with small diameter glass fibers (i.e., fibers having an average fiber diameter of 15HT or less) to achieve preferred fiber orientation and product structure. The fiberglass insulation products surprisingly demonstrate improved thermal performance and overall material efficiency.
[0034] The fibrous insulation products of the present invention are comprised of a plurality of fibers, such as organic or inorganic fibers. In certain exemplary embodiments, the plurality of fibers are inorganic fibers, including, but not limited to, glass fibers, glass wool fibers, mineral wool fibers, slag wool fibers, stone wool fibers, ceramic fibers, metal fibers, and combinations thereof.
[0035] Optionally, the fibers may include natural and / or synthetic fibers, such as carbon, polyester, polyethylene, polyethylene terephthalate, polypropylene, polyamide, aramid, and / or polyaramid fibers. As used herein, the term "natural fibers" refers to plant fibers extracted from any part of a plant, including, but not limited to, stems, seeds, leaves, roots, or phloem. Examples of natural fibers suitable for use in insulation products include wood fibers, cellulose fibers, straw, wood chips, wood strands, cotton, jute, bamboo, ramie, bagasse, hemp, coir, linen, kenaf, sisal, flax, henequen, and combinations thereof. A fiber insulation product may be made entirely of one type of fiber or may be formed from a combination of various fibers. For example, a fiber insulation product may be formed from a combination of various glass fibers or various combinations of various inorganic and / or natural fibers depending on the desired insulation application. For any of the embodiments disclosed herein, the insulation product may be made substantially or entirely of glass fibers.
[0036] Fiber insulation products utilize glass fibers with smaller diameters than those used in conventional fiberglass insulation products, particularly residential insulation products, which typically have fiber diameters greater than 4 μm (15.7 HT). Specifically, exemplary fiber insulation products disclosed or suggested herein may have glass fibers with an average fiber diameter of 3.81 μm (15 HT) or less prior to application of the binder composition, including average fiber diameters of 3.76 μm (14.8 HT) or less, 3.68 μm (14.5 HT) or less, 3.61 μm (14.2 HT) or less, 3.56 μm (14 HT) or less, 3.43 μm (13.5 HT) or less, 3.30 μm (13 HT) or less, 3.18 μm (12.5 HT) or less, and 3.05 μm (12 HT) or less. For any of the exemplary embodiments, the fibrous insulation product may include glass fibers having an average fiber diameter ranging from 3.05 μm (12.0HT) to 3.81 μm (15.0HT), from 3.30 μm (13.0HT) to 3.76 μm (14.8HT), or from 3.43 μm (13.5HT) to 3.61 μm (14.2HT). In other exemplary embodiments, the insulation product may include glass fibers having an average fiber diameter ranging from 2.03 μm (8.0HT) to 3.05 μm (12.0HT), from 2.29 μm (9.0HT) to 2.79 μm (11.0HT), or from 2.03 μm (8.0HT) to 2.54 μm (10.0HT).
[0037] An exemplary procedure used to measure the diameter of glass fibers utilizes a scanning electron microscope (SEM) to directly measure fiber diameter. Generally, a test piece of a fiber insulation product is heated to remove any organic material (e.g., binder composition) from the test piece, and then the length of the glass fibers from the test piece is reduced and photographed by the SEM. The fiber diameter is then measured from the image saved by image processing software associated with the SEM.
[0038] Specifically, a test specimen of the fiber insulation product is heated to 800°F (426.7°C, where °F = (°F - 32) x (5 / 9)) for a minimum of 30 minutes. The specimen can be heated longer, if necessary, to ensure the removal of any organic material. The specimen is then cooled to room temperature, and the glass fibers are reduced in length so that they can be mounted on an SEM planchette. The glass fibers can be reduced in length by any suitable method, such as by cutting with scissors, cutting with a razor blade, or grinding with a mortar and pestle. The glass fibers are then attached to the surface of the SEM planchette so that they do not overlap or are spaced too far apart.
[0039] Once the specimen is prepared for imaging, it is mounted in the SEM using standard operating procedures and photographed by the SEM at a magnification appropriate for the diameter size of the fiber being measured. A sufficient number of images are collected and stored so that a sufficient number of fibers are available for measurement. For example, 10-13 images may be required, resulting in 250-300 fibers being measured. The fiber diameters are then measured using an SEM image analysis software program, such as Scandium SIS Imaging Software. The average fiber diameter of the specimen is then calculated from the number of fibers measured. Fiber insulation product specimens may include glass fibers that are fused together (i.e., two or more fibers are joined along their length). For purposes of calculating the average fiber diameter of the specimen in this disclosure, fused fibers are treated as a single fiber.
[0040] Another procedure used to measure the average fiber diameter of glass fibers utilizes an airflow resistance measurement device to indirectly determine the average or "effective" fiber diameter of randomly distributed fibers in a test specimen. Specifically, in one example of this procedure, a test specimen of a fibrous insulation product is heated to 800-1000°F (426.7-537.8°C) for 30 minutes. The test specimen is heated longer, if necessary, to remove any organic material. The test specimen is then cooled to room temperature, and a test specimen weighing approximately 7.50 grams is placed in the chamber of the device. A constant airflow is introduced into the chamber, and once the airflow has stabilized, the differential pressure or pressure drop is measured by the device. Based on the airflow rate and differential pressure, the device can compute the average fiber diameter of the test specimen.
[0041] The fibrous insulation products of the present invention comprise a "formaldehyde-free" or "formaldehyde-free" aqueous binder composition used to bind inorganic fibers together during the manufacture of the insulation product. "Binder composition" refers to an organic agent or chemical, often a polymeric resin, used to bind inorganic fibers together into a three-dimensional structure. The binder composition can be in any form, such as a solution, emulsion, or dispersion. Thus, "binder dispersion" or "binder emulsion" refers to a mixture of binder chemicals in a medium or vehicle. As used herein, the terms "binder composition," "aqueous binder composition," "binder formulation," "binder," and "binder system" can be used interchangeably and are synonymous. Additionally, as used herein, the terms "formaldehyde-free" or "formaldehyde-free" can be used interchangeably and refer to a binder composition that contains less than about 1 ppm formaldehyde when cured or otherwise dried. 1 ppm is based on the weight of the product being measured for formaldehyde emissions.
[0042] A wide variety of binder compositions can be used with the glass fibers of the present invention. For example, binder compositions are divided into two broad, mutually exclusive classes: thermoplastic and thermosetting. Both thermoplastic and thermosetting binder compositions can be used in the present invention. Thermoplastic materials can be repeatedly heated to a softened or molten state, and such thermoplastic materials return to their previous state upon cooling. In other words, heating can cause a reversible change in the physical state of the thermoplastic material (e.g., from solid to liquid), but the thermoplastic material does not undergo any irreversible chemical reaction. Exemplary thermoplastic polymers suitable for use in the fiber insulation product 100 include, but are not limited to, polyvinyls (e.g., polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, and the like), polyethylene terephthalate (PET), polypropylene or polyphenylene sulfide (PPS), nylon, polycarbonate, polystyrene, polyamides, polyolefins, acrylic and methacrylic acid ester resins, and certain copolymers of polyacrylates.
[0043] In contrast, the term thermoset polymer refers to a range of systems that initially exist as liquids but, upon heating, undergo a reaction to form a solid, highly crosslinked matrix. Thus, thermoset compounds contain a reaction system, often a pair of reactants, that irreversibly crosslinks upon heating. Upon cooling, thermoset compounds do not revert to their previous liquid state but remain in an irreversibly crosslinked state.
[0044] Reactants useful as thermosetting compounds generally contain one or more of several reactive functional groups, such as amine, amide, carboxyl, or hydroxyl groups. As used herein, "thermosetting compound" (and its derivatives, such as "thermosetting compound," "thermosetting binder," or "thermoset binder") refers to at least one of such reactants, although it will be appreciated that more than one may be required to form the crosslinked system characteristic of a thermosetting compound. In addition to the primary reactant in a thermosetting compound, catalysts, processing aids, and other additives may be present.
[0045] One category of thermosetting binders includes various phenol-aldehyde, urea-aldehyde, melamine-aldehyde, and other condensation polymerization materials. Phenolic / formaldehyde binder compositions are known thermosetting binder systems and have historically been favored because they are inexpensive and can transition from a low viscosity liquid in the uncured state to a hard thermosetting polymer upon curing.
[0046] The formaldehyde-free thermosetting binder system may include a binder system based on a polycarboxy polymer and a polyol. One example is the polyacrylic acid / polyol / polyacid binder system described in U.S. Patent Nos. 6,884,849 and 6,699,945 to Chen et al., each of which is incorporated herein by reference in its entirety. Another example is the polycarboxylic acid polymer / long-chain polyol / short-chain polyol binder system described in U.S. Patent Application Publication No. 2019 / 0106564 to Zhang et al., which is incorporated herein by reference in its entirety. Another example is the polycarboxylic acid polymer / monomer polyol binder system described in U.S. Provisional Patent Application No. 63 / 086,267, which is incorporated herein by reference in its entirety. Yet another example is the polycarboxylic acid / polyol / nitrogen-based protectant binder system described in U.S. Provisional Patent Application No. 63 / 073,013, the disclosure of which is incorporated herein by reference in its entirety.
[0047] A second category of formaldehyde-free thermosetting binder compositions is called "bio" or "natural" binders. The terms "biobinder" and "natural binder" are used interchangeably herein to refer to binder compositions made with nutrient compounds, such as carbohydrates, proteins, or fats, that have multiple reactive functionalities. Because these binders are made with nutrient compounds, they are environmentally friendly. Biobinder compositions are described in detail in U.S. Patent Application Publication No. 2011 / 0086567, filed October 8, 2010, by Hawkins et al., which is incorporated herein by reference in its entirety.
[0048] In some exemplary embodiments, the binder comprises an Owens Corning Eco-Touch™ binder or EcoPure™ binder, an Owens Corning Sustaina™ binder, or a Knauf ECOSE® binder.
[0049] Another reactant useful as a thermosetting compound is the triammonium citrate-D-glucose system, which is derived from the combination of D-glucose monohydrate, anhydrous citric acid, water, and aqueous ammonia. Additionally, carbohydrate reactants and polyamine reactants are useful thermosetting compounds, and such thermosetting compounds are described in detail in U.S. Patent Nos. 8,114,210, 9,505,883, and 9,926,464, which are incorporated by reference in their entireties.
[0050] It has surprisingly been found that fibrous insulation products made with glass fibers having an average fiber diameter of less than 15 HT have improved properties when made with a formaldehyde-free binder composition comprising a polyol and a primary crosslinking agent, such as a polycarboxylic acid or its salt. Particularly noteworthy improvements have been found when the polyol contained in the binder composition is a monomeric polyol.
[0051] The primary crosslinker may be any compound suitable for crosslinking polyols. Non-limiting examples of suitable crosslinkers include polycarboxylic acid-based materials having one or more carboxyl groups (—COOH), such as polycarboxylic acid monomers and polycarboxylic acid polymers, including salts and anhydrides of these acids, and mixtures thereof. For any of the exemplary embodiments, the polycarboxylic acid may be a polymerized polycarboxylic acid, such as a homopolymer or copolymer of acrylic acid. Polymerized polycarboxylic acids may include polyacrylic acid (its salts or anhydrides) and polyacrylic acid-based resins, such as QR-1629S and Acumer 9932 (both commercially available from The Dow Chemical Company), polyacrylic acid compositions commercially available from CH Polymers, and polyacrylic acid compositions commercially available from Coatex. Acumer 9932 is a polyacrylic acid / sodium hypophosphite resin with a molecular weight of approximately 4000 and a sodium hypophosphite content of 6-7% by weight, based on the total weight of the polyacrylic acid / sodium hypophosphite resin. QR-1629S is a polyacrylic acid / glycerin resin composition. Aquaset-529 is a composition comprising polyacrylic acid crosslinked with glycerol.
[0052] The polycarboxylic acids may include polymeric polycarboxylic acids, such as polyacrylic acid, poly(meth)acrylic acid, polymaleic acid, and similar polymeric polycarboxylic acids, anhydrides, salts, or mixtures of such acids, as well as acrylic acid, methacrylic acid, maleic acid, and similar carboxylic acids, anhydrides, salts, and mixtures of such acids.
[0053] For any of the exemplary embodiments, the polycarboxylic acid may include polycarboxylic acid monomers such as citric acid, itaconic acid, maleic acid, fumaric acid, succinic acid, adipic acid, glutaric acid, tartaric acid, trimellitic acid, hemimellitic acid, trimesic acid, tricarballylic acid, and the like, including salts, anhydrides, and mixtures thereof.
[0054] The crosslinker may, in some cases, be pre-neutralized with a neutralizing agent. Such neutralizing agents include organic and / or inorganic bases, such as sodium hydroxide, ammonium hydroxide, and diethylamine, and any type of primary, secondary, or tertiary amine (alkanolamine). In various exemplary embodiments, the neutralizing agent may include at least one of sodium hydroxide and triethanolamine.
[0055] The crosslinker is present in the binder composition in an amount of at least 30.0 wt.%, based on the total solids content of the binder composition, including, but not limited to, at least 40 wt.%, at least 45 wt.%, at least 50 wt.%, at least 52.0 wt.%, at least 54.0 wt.%, at least 56.0 wt.%, at least 58.0 wt.%, and at least 60.0 wt.%. For any of the embodiments disclosed herein, the crosslinker is present in the aqueous binder composition in an amount of 30 wt.% to 85 wt.%, based on the total solids content of the aqueous binder composition, including, but not limited to, 50.0 wt.% to 70.0 wt.%, greater than 50 wt.% to 65 wt.%, 52.0 wt.% to 62.0 wt.%, greater than 54.0 wt.% to 60.0 wt.%, and 55.0 wt.% to 59.0 wt.%.
[0056] Optionally, in addition to the polycarboxylic acid crosslinkers described above, the binder composition may alternatively include amine-based reactants, such as ammonium salts (e.g., ammonium salts of polycarboxylic acids), amines, diammonium sulfate, proteins, peptides, amino acids, etc. Such amine-based reactants can participate in Maillard reactions with reducing sugars to produce melanoidins (high molecular weight, furan ring- and nitrogen-containing polymers). Thus, in some exemplary embodiments, the binder composition may include melanoidins produced by reaction of an amine-based reactant with one or more reducing sugars.
[0057] The aqueous binder composition may further include at least one polyol. For any of the exemplary embodiments, the polyol may include a monomeric polyol. The monomeric polyol may include a water-soluble compound having a molecular weight of less than 2,000 daltons (including less than 1,000 daltons, less than 750 daltons, and less than 500 daltons) and at least two hydroxyl (—OH) groups. Exemplary monomeric polyols include glucose, sucrose, ethylene glycol, sugar alcohols, pentaerythritol, primary alcohols, 2,2-bis(methylol)propionic acid, tri(methylol)propane (TMP), 1,2,4-butanetriol, trimethylolpropane, fructose, high fructose corn syrup (HFCS), and short-chain alkanolamines containing at least three hydroxyl groups, such as triethanolamine. For any of the embodiments disclosed herein, the polyol may include at least three hydroxyl groups, at least four hydroxyl groups, or at least five hydroxyl groups.
[0058] Sugar alcohols are understood to mean compounds obtained when the aldo or keto group of a sugar is reduced to the corresponding hydroxyl group (e.g., by hydrogenation). The starting sugar may be selected from monosaccharides, oligosaccharides, and polysaccharides, as well as mixtures of these products, such as syrups, molasses, and starch hydrolysates. The starting sugar may also be a dehydrated form of a sugar. Although sugar alcohols closely resemble starting sugars, they are not sugars, and in particular are not reducing sugars. Thus, for example, sugar alcohols do not have reducing ability and cannot participate in the Maillard reaction characteristic of reducing agents. In some exemplary embodiments, sugar alcohols include glycerol, erythritol, arabitol, xylitol, sorbitol, maltitol, mannitol, iditol, isomaltitol, lactitol, cellobitol, palatinitol, maltotritol, syrups thereof, and mixtures thereof. In various exemplary embodiments, the sugar alcohol is selected from glycerol, sorbitol, xylitol, and mixtures thereof. In some exemplary embodiments, the monomeric polyol is a dimeric or oligomeric condensation product of a sugar alcohol. In various exemplary embodiments, the condensation product of a sugar alcohol is isosorbide. In some exemplary embodiments, the sugar alcohol is a diol or a glycol.
[0059] In some exemplary embodiments, the monomer polyol may be present in the aqueous binder composition in an amount of up to about 70% by weight of total solids, including, but not limited to, up to about 60%, up to about 55%, up to about 50%, up to about 40%, up to about 35%, up to about 33%, up to about 30%, up to about 27%, up to about 25%, and up to 20% by weight of total solids. For some exemplary embodiments, the monomer polyol may be present in the aqueous binder composition in an amount of 2.0% to 65.0% by weight of total solids, including, but not limited to, 5.0% to 40.0%, 8.0% to 37.0%, 10.0% to 34.0%, 12.0% to 32.0%, 15.0% to 30.0%, and 20.0% to 28.0% by weight of total solids.
[0060] In various exemplary embodiments, the crosslinker and monomeric polyol are present in amounts such that the ratio of the number of molar equivalents of carboxyl groups, anhydride groups, or salts thereof to the number of molar equivalents of hydroxyl groups is from about 0.3 / 1 to about 1 / 0.3, e.g., from about 0.5 / 1 to about 1 / 0.5, from about 0.6 / 1 to about 1 / 0.6, from about 0.8 / 1 to about 1 / 0.8, or from about 0.9 / 1 to about 1 / 0.9.
[0061] For any of the embodiments disclosed herein, the binder composition may be free or substantially free of polyols containing fewer than three hydroxyl groups, or free or substantially free of polyols containing fewer than four hydroxyl groups. For any of the embodiments disclosed herein, the binder composition may be free or substantially free of polyols having a number average molecular weight of 2,000 daltons or greater, e.g., a molecular weight of 3,000 daltons to 4,000 daltons. Thus, for any of the embodiments disclosed herein, the binder composition may be free or substantially free of diols, e.g., glycols, triols, e.g., glycerol and triethanolamine, and / or polymeric polyhydroxy compounds, which may be partially or fully hydrolyzed, e.g., polyvinyl alcohol, polyvinyl acetate, or mixtures thereof.
[0062] For any of the embodiments disclosed herein, the aqueous binder composition may comprise or consist of a crosslinker based on a polymeric polycarboxylic acid and a monomeric polyol with at least four hydroxyl groups, with a ratio of carboxylic acid groups to hydroxyl OH groups of 0.60 / 1 to 1 / 0.6.
[0063] However, in some exemplary embodiments, the polyol may comprise a polymeric polyol having at least two hydroxyl groups and a number average molecular weight of at least 2,000 Daltons. The polymeric polyol may be included as the only polyol in the binder composition, or the polymeric polyol may be included as a secondary polyol in addition to the monomeric polyols described above.
[0064] In some exemplary embodiments, the secondary polyol comprises one or more of a polymerized polyhydroxy compound, such as polyvinyl alcohol, polyvinyl acetate, which may be partially or fully hydrolyzed, or mixtures thereof. By way of example, when partially hydrolyzed polyvinyl acetate serves as the polyol component, 80% to 89% hydrolyzed polyvinyl acetate, such as Poval® 385 (Kuraray America, Inc.) and Sekisui Specialty Chemicals America, LLC, may be utilized, which are approximately 85% (Poval® 385) and approximately 88% (Selvol™ 502), respectively. Another option is ELVANOL 51-05, or other partially hydrolyzed polyvinyl acetate, available from DuPont and having a molecular weight of about 22,000 to about 26,000 daltons and a viscosity of about 5.0 to 6.0 centipoise.
[0065] The secondary polyol may be present in the aqueous binder composition in an amount of up to about 30% by weight of total solids, including, but not limited to, up to about 28%, up to about 25%, up to about 20%, up to about 18%, up to about 15%, and up to about 13% by weight of total solids. For any of the exemplary embodiments, the secondary polyol may be present in the aqueous binder composition in an amount of 2.5% to 30% by weight of total solids, including, but not limited to, 5% to 25%, 8% to 20%, 9% to 18%, and 10% to 16% by weight of total solids.
[0066] In such binder composition embodiments containing a secondary polyol, the ratio of the number of molar equivalents of carboxylic acid groups, anhydride groups, or salts thereof to the number of molar equivalents of hydroxyl groups in the crosslinker, monomeric polyol, and secondary polyol is about 1 / 0.05 to about 1 / 5, e.g., about 1 / 0.08 to about 1 / 2.0, about 1 / 0.1 to about 1 / 1.5, and about 1 / 0.3 to about 1 / 0.66. Within this ratio range, the ratio of secondary polyol to monomeric polyol affects the performance of the binder composition, such as the tensile strength and water solubility of the binder after curing. For example, a ratio of secondary polyol to monomeric polyol of about 0.1 / 0.9 to about 0.9 / 0.1, e.g., about 0.3 / 0.7 to about 0.7 / 0.3, or about 0.4 / 0.6 to about 0.6 / 0.4, can provide a desirable balance of mechanical and physical color properties. In various exemplary embodiments, the ratio of secondary polyol to monomeric polyol is about 0.5 / 0.5.
[0067] For any of the aqueous binder compositions disclosed herein, all or a portion of the acid functionality of the polycarboxylic acid can be temporarily blocked with a blocking agent, which temporarily prevents the acid functionality from complexing with the mineral wool fibers. The blocking agent is then removed during the curing process by heating the binder composition to a temperature of at least 150°C to eliminate the acid functionality, crosslink with the polyol component, and complete the esterification process. For any of the exemplary embodiments, 10% to 100% of the carboxylic acid functionality can be temporarily blocked with a blocking agent, including about 25% to about 99%, about 30% to about 90%, about 40% to 85%, and all subranges and combinations therebetween. For any of the exemplary embodiments, at least 40% of the acid functionality can be temporarily blocked with a blocking agent.
[0068] The protective agent can reversibly bond to the carboxylic acid group of the crosslinker. For any of the exemplary embodiments, the protective agent includes any compound containing a molecule capable of forming at least one reversible ionic bond with a single acid functional group. For any of the exemplary embodiments disclosed herein, the protective agent can include a nitrogen-based protective agent, such as an ammonia-based protective agent, an amine-based protective agent, or a mixture thereof. An exemplary ammonia-based protective agent includes ammonium hydroxide. An exemplary amine-based protective agent includes alkylamines and diamines, such as ethyleneimine, ethylenediamine, hexamethylenediamine, alkanolamines, such as ethanolamine, diethanolamine, triethanolamine, ethylenediamine-N,N'-disuccinic acid (EDDS), ethylenediaminetetraacetic acid (EDTA), or mixtures thereof. Additionally, alkanolamines can be used as both protective agents and participants in the crosslinking reaction to form esters in the cured binder. Thus, the alkanolamine has the dual function of a protective agent and a polyol to crosslink with polycarboxylic acids via esterification.
[0069] Protecting agents function differently from conventional pH adjusters. Protecting agents, as defined herein, only temporarily and reversibly block acid functional groups in polymeric polycarboxylic acid components. In contrast, conventional pH adjusters, such as sodium hydroxide, permanently terminate the acid functional groups, thereby preventing crosslinking between the acid and carboxyl groups resulting from the blocked acid functional groups. Thus, the inclusion of traditional pH adjusters, such as sodium hydroxide, does not achieve the desired effect of temporarily blocking the acid functional groups, while later liberating these functional groups during curing to enable crosslinking via esterification. Therefore, for any of the exemplary embodiments disclosed herein, the binder composition may be free or substantially free of conventional pH adjusters, such as sodium hydroxide and calcium hydroxide. Such conventional pH adjusters for high-temperature applications permanently bond with carboxylic acid groups and do not free them to eliminate carboxylic acid group functionality to enable crosslinking esterification.
[0070] Any of the binder compositions disclosed herein may further include an additive blend containing one or more processing aids that improve the processability of the binder composition by reducing the binder's viscosity and tack, resulting in a uniform insulation product with increased tensile strength and hydrophobicity. While various additives can reduce the viscosity and / or tack of a binder composition, traditional additives are hydrophilic in nature, and therefore, the inclusion of such additives increases the overall water absorption of the binder composition. The additive blend may include one or more processing aids. Examples of processing aids include surfactants, glycerol, 1,2,4-butanetriol, 1,4-butanediol, 1,2-propanediol, 1,3-propanediol, poly(ethylene glycol) (e.g., Carbowax™), monooleate polyethylene glycol (MOPEG), silicone, polydimethylsiloxane (PDMS) dispersions, mineral, paraffin, or vegetable oil emulsions and / or dispersions, waxes such as amide waxes (e.g., ethylene bis-stearamide (EBS)) and carnauba wax (e.g., ML-155), hydrophobized silica, ammonium phosphate, or combinations thereof. Surfactants include nonionic surfactants, including those with alcohol functionality. Exemplary surfactants include Surfynol®, alkyl polyglucosides (e.g., Glucopon®), and alcohol ethoxylates (e.g., Lutensol®).
[0071] The additive blend can include a single processing aid, a mixture of at least two processing aids, a mixture of at least three processing aids, or a mixture of at least four processing aids. For any of the embodiments disclosed herein, the additive blend can include a mixture of glycerol and polydimethylsiloxane.
[0072] The additive blend may be present in the binder composition in an amount of 1.0 wt.% to 20 wt.%, 1.25 wt.% to 17.0 wt.%, 1.5 wt.% to 15.0 wt.%, about 3.0 wt.% to 12.0 wt.%, or 5.0 wt.% to 10.0 wt.%, based on the total solids content of the binder composition. In any of the exemplary embodiments, the binder composition may include at least 7.0 wt.% of the additive blend, based on the total solids content of the binder composition, including at least 8.0 wt.% and at least 9 wt.%. Thus, in any of the exemplary embodiments, the aqueous binder composition may include 7.0 wt.% to 15 wt.% of the additive blend, based on the total solids content of the binder composition, including 8.0 wt.% to 13.5 wt.%, 9.0 wt.% to 12.5 wt.%.
[0073] In embodiments in which the additive blend includes glycerol, the glycerol may be present in an amount of at least 5.0 wt%, at least 6.0 wt%, at least 7.0 wt%, or at least 7.5 wt%, based on the total solids in the binder composition. For any of the exemplary embodiments, the binder composition may include 5.0% to 15% by weight of glycerol, including 6.5% to 13.0% by weight, 7.0% to 12.0% by weight, or 7.5% to 11.0% by weight, based on the total solids in the binder composition.
[0074] In embodiments in which the additive blend includes polydimethylsiloxane, the polydimethylsiloxane may be present in an amount of at least 0.2 wt%, at least 0.5 wt%, at least 0.8 wt%, or at least 1.0 wt%, at least 1.5 wt%, or at least 2.0 wt%, based on the total solids in the binder composition. For any of the exemplary embodiments, the binder composition may include from 0.5 wt% to 5.0 wt% polydimethylsiloxane, based on the total solids in the binder composition, including from 1.0 wt% to 4.0 wt%, from 1.2 wt% to 3.5 wt%, from 1.5 wt% to 3.0 wt%, and from 1.6 wt% to 2.3 wt%.
[0075] For any of the embodiments disclosed herein, the additive blend may comprise a mixture of glycerol and polydimethylsiloxane, where the glycerol comprises 5.0-15% by weight of the binder composition and the polydimethylsiloxane comprises 0.5-5.0% by weight of the binder composition, based on the total solids content of the binder composition. For any of the embodiments disclosed herein, the additive blend may comprise a mixture of glycerol and polydimethylsiloxane, where the glycerol comprises 7.0-12% by weight of the binder composition and the polydimethylsiloxane comprises 1.2-3.5% by weight of the binder composition, based on the total solids content of the binder composition.
[0076] For any of the embodiments disclosed herein, the additive blend may include an increased concentration of a silane bonding agent. Conventional binder compositions generally contain less than 0.5 wt. % silane, and more typically about 0.2 wt. % or less silane, based on the total solids content of the binder composition. Thus, for any of the embodiments disclosed herein, the silane bonding agent may be present in the binder composition in an amount of 0.5% to 5.0% by weight of the total solids in the binder composition, where 0.5% to 5.0% by weight includes about 0.7% to 2.5%, 0.85% to 2.0%, or 0.95% to 1.5% by weight. For any of the embodiments disclosed herein, the silane bonding agent may be present in the binder composition in an amount of up to 1.0 wt. %.
[0077] Silane concentration may be further characterized by the amount of silane deposited on the fibers in a fiber insulation product. Typically, fiberglass insulation products contain 0.001% to 0.03% by weight of silane binder deposited on the glass fibers. However, by increasing the amount of silane binder contained on the fibers, the amount of silane deposited on the glass fibers increases to at least 0.10% by weight.
[0078] Alternatively, the binder composition may include a conventional amount of a silane bonding agent, if present. In such embodiments, the silane bonding agent may be present in the binder composition in an amount of from 0 to less than 0.5 wt. % by weight of total solids in the binder composition, where 0 to less than 0.5 wt. % includes from 0.05 to 0.4 wt. %, from 0.1 to 0.35 wt. %, or from 0.15 to 0.3 wt. %.
[0079] Non-limiting examples of silane bonding agents that can be used in the binder composition may be characterized by functional groups such as alkyl, allyl, amino, epoxy, vinyl, methacryloxy, ureido, isocyanato, and mercapto groups. In exemplary embodiments, the silane bonding agent includes silanes containing one or more nitrogen atoms with one or more functional groups such as amine groups (primary, secondary, tertiary, and quaternary), amino groups, imino groups, amido groups, imido groups, ureido groups, or isocyanato groups. Specific non-limiting examples of suitable silane coupling agents include, but are not limited to, aminosilanes (e.g., triethoxyaminopropylsilane, 3-aminopropyl-triethoxysilane, and 3-aminopropyl-trihydroxysilane), epoxytrialkoxysilanes (e.g., 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane), methylacryltrialkoxysilanes (e.g., 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane), hydrocarbontrialkoxysilanes, aminotrihydroxysilanes, epoxytrihydroxysilanes, methacryltrihydroxysilanes, and / or hydrocarbontrihydroxysilanes. In one or more exemplary embodiments, the silane is an aminosilane, such as γ-aminopropyltriethoxysilane.
[0080] Any of the aqueous binder compositions disclosed herein may further include an esterification catalyst, also known as a cure accelerator. The catalyst may include inorganic salts, Lewis acids (i.e., aluminum chloride or boron trifluoride), Bronsted acids (i.e., sulfuric acid, p-toluenesulfonic acid, and boric acid), organometallic complexes (i.e., lithium carboxylate, sodium carboxylate), and / or Lewis bases (i.e., polyethyleneimine, diethylamine, or triethylamine). Additionally, the catalyst may include alkali metal salts of phosphorus-containing organic acids, particularly alkali metal salts of phosphoric acid, hypophosphorous acid, or polyphosphoric acid. Examples of such phosphorus catalysts include, but are not limited to, sodium hypophosphite, sodium phosphate, potassium phosphate, disodium pyrophosphate, tetrasodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, potassium phosphate, potassium tripolyphosphate, sodium trimetaphosphate, sodium tetrametaphosphate, and mixtures thereof. Additionally, the catalyst or cure accelerator may be a fluoroborate compound, such as fluoroboric acid, sodium tetrafluoroborate, potassium tetrafluoroborate, calcium tetrafluoroborate, magnesium tetrafluoroborate, zinc tetrafluoroborate, ammonium tetrafluoroborate, and mixtures thereof. Additionally, the catalyst may be a mixture of a phosphorus compound and a fluoroborate compound. Other sodium salts, such as sodium sulfate, sodium nitrate, and sodium carbonate, may also or alternatively be used as catalysts.
[0081] The catalyst may be present in the aqueous binder composition in an amount of from about 0% to about 10% by weight of the total solids of the binder composition, including, but not limited to, from about 1% to about 5%, from about 2% to about 4.5%, from about 2.8% to about 4.0%, or from about 3.0% to about 3.8% by weight.
[0082] Optionally, the aqueous binder composition may include at least one binder. In at least one exemplary embodiment, the binder is a silane binder. The binder may be present in the binder composition in an amount of from about 0.01% to about 5%, from about 0.01% to about 2.5%, from about 0.05% to about 1.5%, or from about 0.1% to about 1.0%, by weight of the total solids of the binder composition.
[0083] Non-limiting examples of silane bonding agents that can be used in the binder composition may be characterized by functional groups such as alkyl, allyl, amino, epoxy, vinyl, methacryloxy, ureido, isocyanato, and mercapto groups. In exemplary embodiments, the silane bonding agent includes silanes containing one or more nitrogen atoms with one or more functional groups such as amine groups (primary, secondary, tertiary, and quaternary), amino groups, imino groups, amido groups, imido groups, ureido groups, or isocyanato groups. Specific non-limiting examples of suitable silane coupling agents include, but are not limited to, aminosilanes (e.g., triethoxyaminopropylsilane, 3-aminopropyl-triethoxysilane, and 3-aminopropyl-trihydroxysilane), epoxytrialkoxysilanes (e.g., 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane), methylacryltrialkoxysilanes (e.g., 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane), hydrocarbontrialkoxysilanes, aminotrihydroxysilanes, epoxytrihydroxysilanes, methacryltrihydroxysilanes, and / or hydrocarbontrihydroxysilanes. In one or more exemplary embodiments, the silane is an aminosilane, such as γ-aminopropyltriethoxysilane.
[0084] The aqueous binder composition may further include a processing aid. The processing aid is not particularly limiting to the present invention, so long as the processing aid functions to facilitate the fiber forming and orientation process. The processing aid may be used to improve binder application distribution uniformity, reduce binder viscosity, increase ramp height after forming, improve vertical weight distribution uniformity, and / or facilitate binder dehydration during both the forming and oven curing processes. The processing aid may be present in the binder composition in an amount of 0 to about 10.0 wt. %, about 0.1 to about 5.0 wt. %, about 0.3 to about 2.0 wt. %, or about 0.5 to 1.0 wt. %, based on the total solids in the binder composition. In some exemplary embodiments, the aqueous binder composition is substantially or completely free of any processing aids.
[0085] Examples of processing aids include defoamers, such as emulsions and / or dispersions of mineral, paraffin, or vegetable oils, polydimethylsiloxane (PDMS) fluids, and dispersions of silica hydrophobized with polydimethylsiloxane or other materials. Other processing aids may include amide waxes, such as ethylene bis-stearamide (EBS), or particles made of hydrophobized silica. Another processing aid that may be utilized in the binder composition is a surfactant. One or more surfactants may be included in the binder composition to aid in binder atomization, wetting, and interfacial adhesion.
[0086] The surfactant is not particularly limited and includes various surfactants, such as ionic surfactants (e.g., sulfates, sulfonates, phosphates, and carboxylates), sulfates (e.g., alkyl sulfates, ammonium lauryl sulfate, sodium lauryl sulfate (SDS), alkyl ether sulfates, sodium laureth sulfate, and sodium myreth sulfate), amphoteric surfactants (e.g., alkyl betaines, such as lauryl betaine), sulfonates (e.g., sodium dioctyl sulfosuccinate, perfluorooctane sulfonate, perfluorobutane sulfonate, and alkyl benzene sulfonate), phosphates (e.g., alkyl aryl ether phosphates and alkyl ether phosphates), carboxylates (e.g., alkyl carboxylates), Examples of surfactants include, but are not limited to, ammonium nitrate, fatty acid salts (soaps), sodium stearate, sodium lauroyl sarcosinate, carboxylate fluorosurfactants, perfluoronanoate and perfluorooctanoate), cations (e.g., alkylamine salts, such as laurylamine acetate), pH-dependent surfactants (primary, secondary or tertiary amines), permanently charged quaternary ammonium cations (e.g., alkyltrimethylammonium salts, cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetylpyridinium chloride and benzethonium chloride) and zwitterionic surfactants, quaternary ammonium salts (e.g., lauryltrimethylammonium chloride and alkylbenzyldimethylammonium chloride) and polyoxyethylene alkylamines.
[0087] Suitable nonionic surfactants that can be used with the binder composition include polyethers (e.g., condensates of ethylene oxide and propylene oxide, including straight- and branched-chain alkyl and alkaryl polyethylene glycol and polypropylene glycol ethers and thioethers), alkylphenoxypoly(ethyleneoxy)ethanols having alkyl groups containing from about 7 to about 18 carbon atoms and having from about 4 to about 240 ethyleneoxy units (e.g., heptylphenoxypoly(ethyleneoxy)ethanol and nonylphenoxypoly(ethyleneoxy)ethanol), polyoxyalkylene derivatives of hexitols, including sorbitan, sorbide, mannitan, and mannide, partial long-chain fatty acid esters (e.g., sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, sorbitan hydroxybenzoates ... polyoxyalkylene derivatives of ethylene oxide, sorbitan monooleate, and sorbitan trioleate; condensations of ethylene oxide with a hydrophobic base, where the base is formed by condensing propylene oxide with propylene glycol; sulfur-containing condensations (e.g., condensations prepared by condensing ethylene oxide with higher alkyl mercaptans, such as nonyl, dodecyl, or tetradecyl mercaptan, or with alkylthiophenols, where the alkyl group contains from about 6 to about 15 carbon atoms); ethylene oxide derivatives of long-chain carboxylic acids (e.g., lauric acid, myristic acid, palmitic acid, and oleic acid, e.g., tall oil fatty acid); ethylene oxide derivatives of long-chain alcohols (e.g., octyl, decyl, lauryl, or cetyl alcohol); and ethylene oxide / propylene oxide copolymers.
[0088] In at least one exemplary embodiment, the surfactant is Dynol 607, which is 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol; SURFONYL® 420, SURFONYL® 440, and SURFONYL® 465, which are ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol surfactants (commercially available from Evonik Corporation, Allentown, Pennsylvania); Stanfax (sodium lauryl sulfate); Surfynol 465 (ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol); Triton™ GR-PG70 (sodium 1,4-bis(2-ethylhexyl) sulfosuccinate); and Triton™ CF-10. (poly(oxy-1,2-ethanediyl), alpha-(phenylmethyl)-omega-(1,1,3,3-tetramethylbutyl)phenoxy).
[0089] Optionally, the aqueous binder composition may include a dust suppressant to reduce or eliminate the presence of inorganic and / or organic particles that may adversely affect the subsequent fabrication and installation of the insulating material. The dust suppressant may be any conventional mineral oil, mineral oil emulsion, natural or synthetic oil, bio-based oil, or lubricating oil, such as, but not limited to, silicones and silicone emulsions, polyethylene glycol, and any petroleum-based or non-petroleum-based oil with a high flash point to minimize evaporation of the oil in the oven.
[0090] The aqueous binder composition may include up to about 15% by weight of the dust suppressant, such as up to about 14% by weight, or up to about 13% by weight. For any of the embodiments disclosed herein, the aqueous binder composition may include 1.0% to 15% by weight of the dust suppressant, such as from about 3.0% to about 13.0% by weight, or from about 5.0% to about 12.8% by weight.
[0091] The aqueous binder composition may optionally contain organic and / or inorganic acids and bases as pH adjusters in an amount sufficient to adjust the pH to a desired level. The pH can be adjusted depending on the intended use to promote compatibility of the binder composition's materials or to function with various types of fibers. In some exemplary embodiments, the pH adjuster is adjusted to adjust the pH of the binder composition to an acidic pH. Examples of suitable acidic pH adjusters include inorganic acids, such as, but not limited to, sulfuric acid, phosphoric acid, and boric acid, as well as organic acids, such as p-toluenesulfonic acid, mono- or polycarboxylic acids, such as citric acid, acetic acid, and their anhydrides, adipic acid, oxalic acid, and their corresponding salts. Inorganic salts, which may also be acid precursors, may also be used. The acid adjusts the pH and, in some cases, acts as a crosslinker, as described above. An organic and / or inorganic base may be included to increase the pH of the binder composition. The base may be a volatile or non-volatile base. Exemplary volatile bases include, for example, ammonia and alkyl-substituted amines such as methylamine, ethylamine or 1-aminopropane, dimethylamine, and ethylmethylamine. Exemplary non-volatile bases include, for example, sodium hydroxide, potassium hydroxide, sodium carbonate, and t-butylammonium hydroxide.
[0092] For any of the exemplary embodiments, in the uncured state, the binder composition may have an acidic pH, e.g., a pH in the range of about 2.0 to about 5.0, including all values and ranges therebetween. For any of the embodiments disclosed herein, the pH of the binder composition in the uncured state may be about 2.2-4.0, including ranges of about 2.5-3.8 and about 2.6-3.5. After curing, the pH of the binder composition may increase to a pH of at least 5.0, including levels of about 6.5-8.8 or about 6.8-8.2.
[0093] Alternatively, the binder composition may be adjusted to a more alkaline pH, such as a pH of about 5 to about 10, a pH of about 6 to about 9, or a pH of about 7 to about 8, in the uncured state.
[0094] The binder further comprises water to dissolve or disperse the active solids for application to the reinforcing fibers. Water may be added in an amount sufficient to dilute the aqueous binder composition to a viscosity suitable for application to the reinforcing fibers and to achieve a desired solids content on the fibers. It has been found that the binder compositions of the present invention can contain lower solids contents than traditional phenolic-urea-formaldehyde or carbohydrate-based binder compositions. In particular, the binder compositions can contain 5% to 35% by weight of binder solids, including amounts ranging from 10% to 30%, 12% to 20%, and 15% to 19% by weight of binder solids. This level of solids indicates that the binder compositions of the present invention can contain more water than conventional binder compositions.
[0095] Table 1 below lists exemplary binder compositions containing the materials described above. The exemplary compositions listed in Table 1 may include optional additives or materials described above. TIFF2024522501000002.tif97153
[0096] An exemplary fiber insulation product 100 is shown in FIG. 1. The fiber insulation product 100 can be configured in a variety of ways. In the exemplary embodiment of FIG. 1, the fiber insulation product 100 is a generally box-shaped fiberglass insulation batt, but the insulation product may be of any suitable shape or size, such as a rolled product or blanket. As an insulation batt or blanket, the fiber insulation product 100 may be placed within an insulation cavity of a building. For example, the fiber insulation product 100 may be placed within the space or cavity between two parallel, spaced-apart framing members in the wall, roof, or floor framing of a building.
[0097] The fibrous insulation product 100 includes an insulating layer 102 having nonwoven glass fibers and a binder composition for holding the glass fibers together. Optionally, the fibrous insulation product 100 may further include a facing or facing material (surface finish) 104 attached or otherwise affixed to the insulating layer 102. The fibrous insulation product 100 has a first side 106, a second side 108 opposite and spaced apart from the first side 106, a third side 110 extending between the first side 106 and the second side 108, and a fourth side 112 opposite and spaced apart from the third side 110 and extending between the first side 106 and the second side 108. The fibrous insulation product 100 further has a first face 114 connecting the sides 106, 108, 110, and 112 to one another and a second face 116 located opposite and parallel to or generally parallel to the first face 114 and connecting the sides 106, 108, 110, and 112 to one another. In an uncompressed state, the fibrous insulation product 100 has a length L1, a width W1, and a thickness T1. In some embodiments, the length L1 is greater than the width W1, and the width W1 is greater than the thickness T1.
[0098] The facing 104 can be placed on the insulation layer 102 to cover all or a portion of the first face 114, the second face 116, or both faces of the fiber insulation product 100. The facing 104 can take a wide variety of forms. The facing 104 can be a single piece of material or multiple different pieces or sheets of material, and such a facing can include a single layer of material or several layers of material. In the illustrated embodiment of FIG. 1, the facing 104 is a single piece of material that covers all of the first face 114 of the fiber insulation product 100.
[0099] The facing 104 can be constructed from a wide variety of materials. Any material suitable for use in fiber insulation products can be used. For example, the facing 104 can be constructed from a nonwoven fiberglass and polymer medium, a polymeric medium, a woven fiberglass and polymeric medium, a facing material, such as a polymeric facing film, a scrim, a cloth, a woven fabric, fiberglass reinforced kraft paper (FRK), a foil-scrim-kraft paper laminate, recycled paper, or calendered paper.
[0100] A significant amount of insulation placed within a building's insulation cavity is in the form of an insulation blanket rolled from an insulation product, such as the insulation products described herein. The faced insulation product is installed with the facing 104 positioned flat on the edge of the insulation cavity, typically on the inside of the insulation cavity. In general, insulation products whose facing is a vapor barrier are commonly used to insulate wall, floor, or ceiling cavities that separate a warm interior space from a cooler exterior space. The vapor barrier is placed on one side of the insulation product to slow or prevent the movement of water vapor through the insulation product.
[0101] FIG. 2 illustrates an exemplary embodiment of an apparatus 118 for manufacturing the fiber insulation product 100. The fiber insulation product 100 may be manufactured in a continuous process by fiberizing molten glass, coating the molten glass fibers with a binder, forming a fiberglass pack on a porous moving conveyor (also called a "forming chain"), and curing the binder to form the insulation blanket, as shown in FIG. 2. The glass may be melted in a tank (not shown) and fed to a fiber-forming device, such as one or more fiberizing spinners 119. While the spinners 119 are shown as fiber-forming devices in the illustrated embodiment, it will be understood that other types of fiber-forming units may be used to form the fiber insulation product 100. The spinners 119 are rotated at high speeds. Centrifugal force forces the molten glass through small orifices in the circumferential sidewall of the fiberizing spinners 119, forming glass fibers. Random length glass fibers 130 may be allowed to fall off the fiberizing spinner 119 and blown generally downward (i.e., generally perpendicular to the plane of the spinner 119) by a blower 120 positioned within the forming chamber 125.
[0102] The blower 120 redirects the glass fibers 130 downward. As the glass fibers 130 pass downward through the forming chamber 125 and are still hot due to the drawing operation, they are blown by the annular spray ring 135 with the aqueous binder composition, resulting in a relatively uniform distribution of the binder composition throughout the glass fibers 130. Water can also be applied, for example by spraying, to the glass fibers 130 in the forming chamber 125 to at least partially cool the glass fibers 130 prior to application of the binder composition.
[0103] The glass fibers 130, with the uncured aqueous binder composition attached thereto, may be collected and formed into a fiber pack 140 on an endless forming conveyor 145 within the forming chamber 125, assisted by a vacuum (not shown) drawn through the fiber pack 140 from beneath the forming conveyor 145. During the forming operation, residual heat from the airflow through the glass fibers 130 and fiber pack 140 is generally sufficient to volatilize most of the water from the binder, after which the glass fibers 130 exit the forming chamber 125, leaving the remaining components of the binder composition on the glass fibers 130 as a viscous or semi-viscous high-solids liquid.
[0104] The resin-coated fiber pack 140, in its compressed state due to the flow of air through the fiber pack 140 in the forming chamber 125, is then transported from the forming chamber 125 under exit rollers 150 to a transfer zone 155, where the fiber pack 140 expands vertically due to the resilience of the glass fibers 130. The expanded fiber pack 140 is then heated, for example, by conveying the fiber pack 140 into a curing oven 160, where heated air is blown into the fiber pack 140 to evaporate any remaining water in the binder composition, cure the binder composition, and firmly bind the glass fibers 130 together. The curing oven 160 has a perforated upper oven conveyor 165 and a perforated lower oven conveyor 170 that draw the fiber pack 140 between the conveyors 165, 170. Heated air is forced by fan 175 through lower oven conveyor 170, fiber pack 140, and upper oven conveyor 165. The heated air exits curing oven 160 through exhaust 180.
[0105] Additionally, within the curing oven 160, the fiber pack 140 may be compressed by upper and lower perforated oven conveyors 165, 170 to form the insulating layer 102 of fibrous insulation fabric 100. The upper and lower oven conveyors 165, 170 may be used to compress the fiber pack 140 to provide the insulating layer 102 with its predetermined thickness T1. It should be understood that although Figure 2 shows the conveyors 165, 170 in a substantially parallel orientation, the conveyors may alternatively be positioned at an angle relative to one another (not shown).
[0106] The cured binder composition provides strength and resilience to the insulation layer 102. It should be understood that drying and curing of the binder composition can be performed in either one step or two separate steps. A two-stage (two-step) process is commonly referred to as B-staging. The curing oven 160 can be operated at a temperature between 100°C and 325°C or between 250°C and 300°C. The fiber pack 140 can remain in the curing oven 160 for a period of time sufficient to crosslink (cure) the binder composition and form the insulation layer 102.
[0107] Once the insulation layer 102 exits the curing oven 160, a facing 193 may be placed on the insulation layer 102 to form the facing layer 104. The facing 193 may be attached to the first face 114, the second face 116, or both faces of the insulation layer 102 by a binder (not shown) or by some other means (e.g., stitching, mechanical interlocking) to form the fiber insulation product 100. Suitable binders include adhesives, polymer resins, asphalt, and bituminous materials that may be coated or otherwise applied to the facing 193. The fiber insulation product 100 may then be wound for storage and / or shipping or cut to length by a cutting device (not shown). It should be understood that in some exemplary embodiments, the insulation layer 102 exiting the curing oven 160 is wound onto a take-up roll or cut into desired length sections and is not surfaced with the facing 193.
[0108] It has surprisingly been discovered that ultrafine glass fibers having a diameter of less than 3.81 microns, or 15HT, can be utilized at lower product weights and thicknesses than anticipated to produce fibrous insulation products with desirable thermal properties and material efficiency. Insulation products formed with fibers having an average diameter of less than 15HT may hereinafter be referred to interchangeably as "ultrafine fiber" insulation products or "inventive" fibrous insulation products.
[0109] Without wishing to be bound by theory, the unique combination of ultra-fine fibers less than 15HT in diameter, a low-viscosity formaldehyde-free binder composition, and certain processing parameters facilitates the orientation of more fibers (or fiber segments) within a certain range of angles along a plane generally parallel to the forming chain (referred to herein as the L1 direction or machine direction). Accordingly, fibrous insulation products of the present invention made from these combinations have a more aligned fiber orientation along the L1 direction than is found in otherwise equivalent insulation products formed with fibers having an average fiber diameter greater than 15HT. Thus, when the fibrous insulation products of the present invention are installed in a wall cavity, ceiling, floor, or similar building structure, the oriented fibers align in a plane more perpendicular to the direction of heat flow, thereby reducing the product's ability to conduct heat through the thickness of the material.
[0110] Figure 3 is an illustration of an SEM image showing the above-described orientation of fibers (or fiber segments) along a plane generally parallel to the plane of the L1 direction. The SEM image was obtained from a microfiber insulation product 200 comprised of glass fibers with an R-value of 22 and an average fiber diameter of 14.5HT, and a formaldehyde-free binder composition containing a monomeric polyol and a polycarboxylic acid crosslinker. The SEM image in Figure 3 shows a 2.5 mm x 1.5 mm product sample with localized fiber vectors (fiber segments in a specific plane).
[0111] Figures 4 and 5 are SEM images further illustrating the fiber insulation product samples. The product sample in Figure 4 is composed of glass fibers with an average fiber diameter of 14.5 HT and an R-value of 22 (hereafter referred to as Sample A), while the product sample in Figure 5 is composed of glass fibers with an average fiber diameter of 16.7 HT and an R-value of 21 (hereafter referred to as Sample B). SEM images of Samples A and B were obtained using a Thermo Scientific Prisma SEM, and the images were stitched together using Thermo Scientific MAPS software. Samples were cut in the machine direction, mounted on SEM stubs using carbon glue and carbon paste, and sputter-coated with Au. Fiber orientation was measured and quantified using the Orientation J plugin from Image J software. The sigma of the Gaussian window was set to 1 pixel, and a Gaussian gradient was selected for the structure tensor.
[0112] The surface area (5.24 mm x 3.14 mm) for each of Sample A and Sample B in the machine direction was imaged and analyzed for orientation distribution. To analyze the orientation distribution, localized glass fibers (or fiber vectors or portions thereof) were measured. Plots of orientation frequency (normalized) versus orientation (degrees) were provided for each sample. Figures 6-8 show the weight percentage of fibers (or fiber vectors or portions thereof) in Sample A within ±50°, ±30°, and ±15° of a common plane (0°) horizontal to the product length L1.
[0113] Surprisingly, an increased proportion of the glass fibers (or fiber vectors or portions thereof) are oriented along a common plane compared to insulation products having the same R-value but including glass fibers with an average diameter greater than 15HT. In particular, for any of the exemplary embodiments, at least 30% by weight of the fibers (or fiber vectors or portions thereof) in the microfiber insulation product can be oriented within ±15° of the common plane. Figure 6 is a graph outlining exemplary fiber orientation distributions within ±15° of the common plane for a fibrous insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5HT. In such embodiments, the microfiber insulation product can comprise or consist of at least 35%, at least 40%, and at least 44% by weight of such fibers (or fiber vectors or portions thereof) oriented within ±15° of the common plane. For any of the exemplary embodiments, the common plane can be a plane parallel to the length and width of the insulation product.
[0114] Furthermore, it has been found that for any of the exemplary embodiments, at least 50% or at least 55% by weight of the glass fibers (or fiber vectors or portions thereof) in the fibrous insulation product may be oriented within ±30° of a common plane. Figure 7 is a graph outlining exemplary fiber orientation distributions within ±30° of a common plane for a fibrous insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5 HT. In such embodiments, the fibrous insulation product may comprise or consist of at least 57%, at least 60%, at least 65%, and at least 69% by weight of the fibers (or fiber vectors or portions thereof) oriented within ±30° of the common plane. For any of the exemplary embodiments, the common plane may be a plane parallel to the length and width of the insulation product.
[0115] In yet another exemplary embodiment, at least 75% by weight of the fibers (or fiber vectors or portions thereof) in the microfiber insulation product are oriented within ±50° of a common plane. FIG. 8 is a graphical representation outlining an exemplary fiber orientation distribution within ±50° of a common plane for a fibrous insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5HT. In such an embodiment, the fibrous insulation product may comprise or consist of at least 78%, at least 80%, at least 82%, and at least 85% by weight of the fibers (or fiber vectors or portions thereof) oriented within ±50° of the common plane. For any of the exemplary embodiments, the common plane may be a plane parallel to the length and width of the insulation product.
[0116] Figure 9(a) is an SEM image showing the fiber orientation of an enlarged sample size area (24 mm x 16 mm) of an exemplary microfiber insulation product (hereinafter referred to as Sample C) formed in accordance with the present invention. Sample C has an R-value of 22 and comprises glass fibers having an average fiber diameter of about 14HT and a formaldehyde-free binder composition containing about 25-30 wt% sorbitol and about 65-70 wt% polyacrylic acid crosslinker, with a viscosity of about 2,000-3,000 cps at 60-65% solids. The aqueous binder composition of Sample C has a viscosity of less than 12,000 cps at a solids content of 74.5% and less than 6,000 cps at a solids content of 70% or less.
[0117] The binder composition in the SEM image in Figure 9(a) was used to measure localized fiber vector orientation (fiber portion viewed at a particular cross section).
[0118] 10(a), by comparison, is an SEM image showing the fiber orientation of a microfiber insulation product having an R-value of 22, also within the scope of the present invention, comprising glass fibers having an average fiber diameter of about 14HT and a formaldehyde-free binder composition containing about 35-45% by weight sorbitol and about 35-45% by weight polyacrylic acid crosslinker, with a viscosity of less than 2,000 cps at 60-65% solids (hereinafter referred to as Sample D). The aqueous binder composition of Sample D has a viscosity of less than 12,000 cps at a solids content of 74.5% and less than 6,000 cps at a solids content of 70% or less.
[0119] SEM images of Samples C and D were acquired using a Thermo Scientific Prisma SEM and stitched together using Thermo Scientific MAPS software. Samples were cut in the machine direction, mounted on SEM stubs using carbon glue and paste, and sputter-coated with Au. Fiber orientation was measured and quantified using the Orientation J plugin from Image J software. The sigma of the Gaussian window was set to 1 pixel, and a Gaussian gradient was selected for the structure tensor.
[0120] A surface area (24 mm x 16 mm) for each of Samples C and D in the machine direction was imaged and analyzed for orientation distribution. As with Samples A and B, localized glass fibers (or fiber vectors or portions thereof) from Samples C and D were measured and analyzed to analyze orientation distribution. Plots of orientation frequency (normalized) versus orientation (degrees) were provided for each sample. Figures 9(b) and 10(b) show the weight percentage of fibers (or fiber vectors or portions thereof) in Samples C and D, respectively, within ±50°, ±30°, and ±15° of a common plane (0°) parallel to the product length L1.
[0121] It was surprisingly found that decreasing the binder viscosity used to form Sample D increased the percentage of glass fibers (or fiber vectors or portions thereof) oriented along a common plane. Specifically, as shown in FIG. 9(b) and in Table 2 below, 32.94 wt. % of the fibers (or fiber vectors or portions thereof) in Sample C were oriented within ±15° of the common plane, 57.07 wt. % were oriented within ±30° of the common plane, and 78.87 wt. % were oriented within ±50° of the common plane. Furthermore, as shown in FIG. 10(b) and in Table 2 below, 45.14 wt. % of the fibers (or fiber vectors or portions thereof) in Sample D were oriented within ±15° of the common plane, 66.23 wt. % were oriented within ±30° of the common plane, and 84.03 wt. % were oriented within ±50° of the common plane. As noted above, the common plane may be a plane parallel to the length and width of the insulation product. TIFF2024522501000003.tif45153
[0122] Additionally, while at least a portion of the fibers (or fiber vectors or portions thereof) in a fibrous insulation product are oriented along a forming chain or plane generally parallel to the "L1 direction," the fibrous insulation product may further include a portion of the fibers (or fiber vectors or portions thereof) oriented along a plane generally perpendicular to the L1 direction. Such "dual orientation" fibrous insulation products demonstrate superior thermal performance while exhibiting improved recovery and / or improved compressive force resistance. Dual orientation fibrous insulation products may have at least 10%, at least 15%, at least 18%, at least 20%, at least 25%, at least 28%, and at least 30% by weight of the fibers (or fiber vectors or portions thereof) oriented along a plane generally perpendicular to the L1 direction.
[0123] In some exemplary embodiments, the fiber insulation product has an increased number of parallel fiber bundles 202, the fiber bundles including at least two fibers oriented in a substantially parallel direction and bundled together at one or more locations along the fiber length. The enlarged SEM images in Figures 11(a)-11(c) show the parallel fiber bundles present in the fiber insulation product. Figures 12(a)-12(c) provide further enlarged SEM images of the fiber insulation product shown in Figure 3, further illustrating the prevalence of parallel fiber bundles. The parallel fiber bundles 202 can form bonds with individual fibers 204 or with other parallel fiber bundles 202.
[0124] For any of the exemplary embodiments, at least 15% by weight of the fibers in the fibrous insulation product 200 may be at least partially contained in parallel fiber bundles. In other exemplary embodiments, at least 20%, at least 25%, at least 28%, at least 30%, at least 35%, at least 40%, at least 45%, and at least 50% by weight of the fibers in the fibrous insulation product may be at least partially contained in parallel fiber bundles.
[0125] Additionally, for any of the exemplary embodiments disclosed herein, the fiber insulation product may have a reduced presence of binder gussets extending between at least two fibers. As defined herein, a binder "gusset" means a portion of the cured binder composition that extends between at least two fibers, typically in a triangular or diamond shape, similar to an angle bracket. Binder gussets are measured by microscopy (e.g., optical microscopy or scanning electron microscopy). With optical microscopy, the use of a refractive index solution to "hide" the glass fibers facilitates identification of the binder-fiber bond and gussets. SEM images showing exemplary binder gussets are provided in Figures 13(a) and 13(b).
[0126] Binder gussets occur between non-parallel fibers, meaning that the fibers are oriented in different planes. Without being bound by theory, it is believed that minimizing binder gussets and increasing the presence of binder composition along the length of the fibers is beneficial in both improving uniform orientation and increasing the presence of parallel fiber bundles.
[0127] Due to increased uniformity in fiber orientation, in some exemplary embodiments, 40% or less by weight of the binder composition present in the fibrous insulation product is contained within the binder gussets. For any of the exemplary embodiments, 35% or less by weight of the binder composition is contained within the binder gussets, including 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, and 5% or less by weight.
[0128] Furthermore, due to increased uniformity in fiber orientation, up to 75% by weight of the binder is contained within binder nodes, which are portions of the binder composition distributed at the intersections between two or more intersecting fibers. In some exemplary embodiments, the amount of binder contained within the binder nodes is limited to up to 60% by weight, including up to 50% by weight, up to 45% by weight, and up to 40% by weight.
[0129] As discussed above, various product and product parameters are believed to affect fiber orientation in microfiber insulation products. Without being bound by theory, it is believed that the increased abundance of fibers (or fiber vectors or portions thereof) oriented generally in a plane parallel to the L1 direction results, at least in part, from the synergistic combination of small diameter glass fibers (i.e., average fiber diameter of 3.81 microns (or 15HT) or less) and a low viscosity formaldehyde-free binder composition. In particular, at a temperature of 25°C, the binder composition has a viscosity of 90,000 cP or less at a solids concentration of 65% to 70% by weight, including viscosities of 50,000 cP or less, 25,000 cP or less, 15,000 cP or less, 10,000 cP or less, and 4,000 cP or less at 25°C and a solids concentration of 65% to 70% by weight.
[0130] In addition to impacting fiber orientation, the low viscosity of the binder composition allows for a reduction in moisture content of the fiber pack on the "ramp" as it moves from the forming chamber into the curing oven. Importantly, the ramp moisture is low enough when the fiber pack enters the curing oven so that the product cures completely and consistently throughout the thickness of the pack. In some exemplary embodiments, the viscosity of the binder composition is adjusted to ensure a ramp moisture level of 7% or less, including levels of 5% or less, 3% or less, and 2% or less.
[0131] The fibrous insulation product has a binder content (LOI: loss on ignition) of the fibrous insulation pack of 10% or less by weight of the fibrous insulation product, 8.0% or less by weight of the fibrous insulation product, 6.0% or less by weight of the fibrous insulation product, or 3.0% or less by weight. For any of the exemplary embodiments, the insulation product has a binder content (LOI) of the fibrous insulation product of 1.0% to 10.0% by weight, including 2.0% to 8.0% by weight, 2.5% to 6.0% by weight, or 3.0% to 5.0% by weight. The relatively small amount of binder contributes to the flexibility of the final insulation product. For any of the exemplary embodiments, the fibrous insulation product has an LOI of less than 4.5%, including less than 4.2%, less than 4.0%, less than 3.8%, and less than 3.5%.
[0132] Without being bound by theory, the orientation of small diameter fibers (i.e., fibers having an average fiber diameter of 15HT or less, or 3.81 microns or less) in a plane generally more parallel to the L1 (or machine) direction plane has resulted in fiber insulation products having surprisingly improved thermal performance and overall material efficiency. The thermal performance of fiberglass insulation products is based on the R-value of the fiberglass insulation product, where R-value is a measure of a product's resistance to heat flow. R-value is determined by the following equation (1): Equation (1): R=T1 / k (1) where "T1" is the thickness of the insulation product in inches, "k" is the thermal conductivity of the insulation product in BTU-inches / (hr·ft²·°F), and "R" is the R-value of the insulation product in (hr·ft²·°F).
[0133] As used herein, the thickness (T1) of the insulation product can be calculated in accordance with ASTM C167-18, and both the k value and area weight (in pounds per square foot) can be calculated in accordance with ASTM C518-17 or ASTM C177-19.
[0134] The R-value, thermal conductivity, and material efficiency of an insulation product are parameters that provide an indication of the thermal performance of the insulation product.
[0135] Material efficiency (“ME”) is calculated using the following equation (2): Equation (2): ME = R value / W where "ME" is R·ft² / lb, where "R" is the R-value of the insulation product and "W" is the areal weight of the insulation product in pounds per square foot. ME measures how efficiently an insulation product resists heat flow and is a metric that can be used to quantify the performance of fiberglass insulation batts. To achieve a high value of R·ft², insulation suppliers typically increase the amount of insulating material (measured in pounds-mass (ib)). Thus, insulation that provides a high R·ft² per pound of material is desirable, as measured by ME (i.e., the insulating effectiveness of the product divided by the amount of material used to provide the insulating effectiveness).
[0136] thermal conductivity The microfiber insulation product of the present invention demonstrated a significantly greater reduction in thermal conductivity than expected for a given density. For example, a 1995 publication by Saint-Gobain (C. Langlais, C., G. Guilbert, G., D. Banner, D., and S. Klarsfeld, S., "Influence of the Chemical Composition of Glass on Heat Transfer through Glass Fiber Insulations in Relation to Their Morphology and Temperature," J. Thermal Insulation and Building Envs., 1995, No. 18, pp. 350-376) (hereinafter referred to as the "SG publication") details a theoretical approach for predicting the thermal performance of fibrous insulations. The SG publication indicates that, in addition to temperature and density, the average fiber diameter has been found to be a means for reducing thermal conductivity, and the SG publication provides data showing the effect of fiber diameter on thermal conductivity. Applicant has developed, independently of the SG publication, proprietary modeling techniques that predict curves nearly identical to those shown in the SG publication. Thus, the data provided in the SG publication (hereinafter the "Predicted Results") are deemed to represent the expected thermal performance of fiberglass insulation at various densities and various fiber diameters.
[0137] However, the thermal conductivity values of the fiberglass insulation product of the present invention having an average fiber diameter of 3.6 microns over a density range of 0.2 pcf to 1.6 pcf are unexpectedly lower than the predicted thermal conductivity values based on the predicted results. Figure 14 shows the difference between the predicted results (based on a fiberglass insulation product having an average fiber diameter of 3 microns) and the measured thermal conductivity values of the 3.6 micron fiberglass insulation product of the present invention. As shown, the thermal conductivity values determined by the predicted results are calculated using the following formula (I): Formula (I) y=0.116x 2 -0.3002x+0.4319 where y is the thermal conductivity (k value) in BTU-in / (hr·ft 2 ·°F) and x is the product density in pounds per cubic foot (“pcf”). Equation (I) corresponds to R 2 =0.9804, which indicates a high degree of accuracy in this equation. In contrast, the measured thermal conductivity values for the 3.6 micron insulation product of the present invention are given by equation (II), i.e., Formula (II) y=0.1013x 2 -0.2438x+0.3763 where y is the thermal conductivity (k value) in BTU-in / (hr·ft 2 ·°F) and x is the product density in pounds per cubic foot or pcf. 2 =0.9803, which indicates a high degree of accuracy in this formula.
[0138] Thus, at a given density, the 3.6 micron insulation product of the present invention demonstrated significantly lower thermal conductivity than would be expected based on an insulation product having a finer average fiber diameter (3.6 microns versus 3.0 microns). For example, at a density of 0.8 pcf, equation (I) yielded a predicted thermal conductivity of 0.2660 BTU-in / (hr·ft 2 ·°F), and the 3.6 micron fiberglass insulation product of the present invention demonstrated a lower measured thermal conductivity (k value) of 0.2461 BTU-in / (hr·ft 2 ·°F). A reduction in k value of 0.0199 is a statistically significant reduction.
[0139] In some embodiments, the fibrous insulation products of the present invention demonstrate a reduction in k-value of at least 0.01 BTU-in / (hr-sq ft-°F) compared to expected results across a density range from 0.2 pcf to 1.35 pcf, including reductions in k-value of at least 0.015 BTU-in / (hr-sq ft-°F), at least 0.03 BTU-in / (hr-sq ft-°F), at least 0.05 BTU-in / (hr-sq ft-°F), at least 0.075 BTU-in / (hr-sq ft-°F), at least 0.1 BTU-in / (hr-sq ft-°F), at least 0.15 BTU-in / (hr-sq ft-°F), at least 0.2 BTU-in / (hr-sq ft-°F), and at least 0.23 BTU-in / (hr-sq ft-°F).
[0140] For any of the exemplary embodiments provided herein, the fibrous insulation product has a thermal insulation capacity, expressed in BTU-in / (hr·ft 2 ·°F), that satisfies the following formula (III): Formula (III): y=0.116x 2 -0.3002x+0.4219 where x is the product density in the range of 0.2 pcf to 1.6 pcf. Equation (III) is based on equation (I), but reduced by 0.01 to ensure sufficient separation for expected results. In these or other exemplary embodiments, the fibrous insulation product, expressed in BTU-in / (hr·ft 2 ·°F), satisfies the following equation (IV): Formula (IV) y=0.1013x 2 -0.2438x+0.3763 where x is the product density in the range of 0.2 pcf to 1.6 pcf.
[0141] While particular advantages can be exemplified in insulation products with low densities (i.e., less than 1.6 pcf), the density of a fibrous insulation product can vary in various embodiments. As used herein, the density of a fibrous insulation product refers to the density of the product after the binder composition has been cured and the cured product is in its free state (i.e., not compressed or stretched). In various embodiments, the density of a fibrous insulation product ranges from 0.2 pcf to 2.7 pcf. Table 3 lists the original densities (in pcf) for various exemplary embodiments of fibrous insulation products having ultrafine fibers ranging from 2.03 μm (8.0 HT) to 3.81 μm (15 HT). In Table 3, fiber diameter refers to the average fiber diameter measured by the airflow resistance method described above prior to application of the binder composition. Thickness and original density refer to the thickness and density of the product after the binder composition has been cured and the cured product is in its free state (i.e., not compressed or stretched). TIFF2024522501000004.tif123153
[0142] The data in Table 3 represent fibrous insulation products with R-values ranging from 11 to 49, produced with an average fiber diameter of 15HT or less, original densities ranging from 0.371 pcf to 1.214 pcf, and binder compositions of 6% or less by weight.
[0143] Material Efficiency As discussed above, material efficiency is a measure of a product's insulating value (R·sq ft) per pound of insulating material, expressed as R·sq ft / lb. By maximizing material efficiency, an insulation product can provide high insulating performance at the lowest possible weight. In other words, the insulation products of the present invention, due to their high material efficiency, can achieve the same insulating performance at a lower weight / density. Reducing product weight reduces the amount of fiberglass and binder material required, thus reducing overall costs (e.g., manufacturing, storage, transportation, and / or disposal costs). Additionally, lower-density products are lighter and easier to handle than higher-density products for the same bag area.
[0144] Unexpectedly, it has been found that the fibrous insulation products of the present invention demonstrate a surprising increase in material efficiency compared to the material efficiency predicted based on predicted results. At high material efficiency, the fibrous insulation products of the present invention can provide the desired thermal insulation performance (R-value) at a lower areal weight than predicted areal weight.
[0145] Figure 15 shows the difference in material efficiency between the predicted results output and the actual material efficiency of a 5.5 inch thick 3.6 micron insulation product of the present invention, based on a fiberglass insulation product with an average fiber diameter of 3 microns and a thickness of 5.5 inches. As shown in Figure 15, the predicted material efficiency of the fiber insulation product as determined by the predicted results is given by the following formula (V): Formula (V) y=35.7480145x 2 -112.2450311x+123.2764898 where y is the material efficiency in R·ft² / lb and x is the product density over a density range from about 0.5 pcf to about 1.5 pcf. Equation (V) corresponds to R 2 =0.9980374, which indicates a high degree of accuracy in the model. In contrast, the actual material efficiency of the 3.6 micron insulation product of the present invention is given by equation (VI), i.e., Formula (VI) y=40.1916068x 2 -120.5813540x+131.7360668 where y is the material efficiency in R·ft² / lb and x is the product density over a density range from about 0.7 pcf to about 1.35 pcf. Equation (VI) corresponds to R 2 =0.9980374, which indicates a high degree of accuracy in this formula.
[0146] At a given density, the 3.6 micron insulation product of the present invention demonstrates a higher material efficiency than predicted based on insulation products having finer fiber average fiber diameters (3.0 microns versus 3.6 microns). For example, at a density of 0.8 pcf, Equation (V) predicts a material efficiency of 56.36 R·sq ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an actual material efficiency of 60.99 R·sq ft / lb, an increase of more than four units. Similarly, at a density of 0.6 pcf, Equation (V) predicts a material efficiency of 68.80 R·sq ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an actual material efficiency of 73.86 R·sq ft / lb, an increase of more than five units.
[0147] Thus, the fibrous insulation products of the present invention demonstrate increased material efficiencies of at least 4.0 units, and in some cases at least 5.0 units, at least 5.5 units, at least 5.8 units, and at least 6.0 units compared to expected material efficiencies across the density range from 0.2 pcf to 1.6 pcf.
[0148] For any of the exemplary embodiments provided herein, the fibrous insulation product can have a material efficiency of at least 50, e.g., at least 55, at least 58, at least 60, at least 63, at least 65, at least 68, at least 70, at least 75, and at least 80, according to the formula ME=R-value / area weight (W), for an R-value of 19 to 24, an areal weight of 0.3 lb / sq ft to 0.5 lb / sq ft, and a density of 0.7 pcf to 1.35 pcf.
[0149] Because individual insulation products may contain certain variations within the product itself, it should be understood that the thermal performance values provided above are provided above average expected values that do not take this natural variation into account. Thus, to account for natural product variations, formula (VI) above may be adjusted by a variation value, which has been calculated as 2.1076693 at a 95% confidence level. Thus, taking this variation value into account, the adjusted material efficiency of the insulation product of the present invention can be calculated using formula (VII), i.e.: Formula (VII) y=40.1916068x 2 -120.5813540x+129.628397 where y is the adjusted material efficiency in R·ft² / lb and x is the product density over a density range from about 0.5 pcf to about 1.5 pcf.
[0150] FIG. 16 graphically illustrates the difference in material efficiency between the predicted output based on a fiberglass insulation product with an average fiber diameter of 3 microns and a thickness of 5.5 inches and the adjusted material efficiency of a 3.6 micron insulation product of the present invention at a thickness of 5.5 inches and including variation variables.
[0151] As shown in Figure 16, the adjusted material efficiency of the 3.6 micron insulation product of the present invention demonstrates a higher material efficiency than predicted results based on insulation products having a finer fiber average fiber diameter (3.6 microns versus 3.0 microns). For example, at a density of 0.8 pcf, Equation (V) (predicted results) predicts a material efficiency of 56.36 R·ft² / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an adjusted material efficiency of 58.89 R·ft² / lb, an increase of more than two units. Similarly, at a density of 0.6 pcf, Equation (V) predicts a material efficiency of 68.80 R·ft² / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an adjusted material efficiency of 71.75 R·ft² / lb, an increase of more than three units.
[0152] While certain benefits can be exemplified for products having various areal weights, certain benefits may be achieved at relatively low areal weights while maintaining desired thermal properties. As used herein, areal weight of a fibrous insulation product is the weight per square foot (lbs / ft) of the insulation product after the binder composition has cured. In various embodiments, the areal weight of the fibrous insulation product ranges from 0.1 lbs / ft to 2.0 lbs / ft, including ranges of 0.2 lbs / ft to 1.8 lbs / ft, 0.25 lbs / ft to 1.5 lbs / ft, 0.3 lbs / ft to 1.2 lbs / ft, 0.35 lbs / ft to 1.0 lbs / ft, and 0.38 lbs / ft to 0.6 lbs / ft. For any of the exemplary embodiments, the area weight of the fiber insulation product may be less than 0.55 pounds per square foot, including less than 0.5 pounds per square foot, less than 0.48 pounds per square foot, less than 0.45 pounds per square foot, and less than 0.42 pounds per square foot.
[0153] Additionally, as noted above, the benefits of improved thermal and material efficiency can be achieved at any insulation product thickness, with particular benefits achieved at relatively low product thicknesses. Generally, to improve the R-value of an insulation product, the thickness (T1) of the insulation product can be increased, thereby reducing the density of the product (assuming no other modifications to the product are made). However, increasing product thickness is not possible for constrained products (i.e., products installed in a wall cavity of a fixed thickness). Therefore, no R-value benefit can be achieved by making the product thicker than the wall cavity thickness, because the insulation product can only expand to the thickness of the wall opening. For any of the exemplary embodiments, the thickness T1 of the fibrous insulation product can be approximately 20 inches or less, including thicknesses of 18 inches or less, 15 inches or less, 12 inches or less, 10 inches or less, 8 inches or less, 7 inches or less, and 6 inches or less. For example, in some thickness constrained products, the fiber insulation product may have a thickness that is less than 7 inches, including less than 6.5 inches, less than 6 inches, less than 5.5 inches, less than 5 inches, less than 4.5 inches, and less than 4 inches. In these or other embodiments, the fiber insulation product may have a thickness of, for example, 0.5 inches to 8 inches, including thicknesses of 0.75 inches to 7.5 inches, 0.9 inches to 7.0 inches, 1.0 inches to 6.8 inches, 1.5 inches to 6.3 inches, and 2.0 inches to 6.0 inches.
[0154] Table 4 shows the structural and thermal properties of two exemplary fiber insulation products (Example 1 and Example 2), which are formed with fibers having average fiber diameters of 14.5HT and 14.4HT, respectively. Each of the products in Example 1 and Example 2 was formed with a formaldehyde-free binder composition including a monomeric polyol and a polymeric polycarboxylic acid crosslinker. Examples 1 and 2 had a thickness of 5.5 inches and an insulation value of R-22. As shown in Table 4 below, at a k value of 0.25 BTU-in / (hr·sq ft·°F), Examples 1 and 2 demonstrated low densities of 0.746 lb / ft3 and 0.759 lb / ft3, respectively, with LOI values of less than 4%. In contrast, Comparative Example 1 was formed with 15.9HT glass fiber and a binder composition including a polymeric polyol and a polycarboxylic acid monomer crosslinker. The product of Comparative Example 1, at a thickness of 5.5 inches and a k-value of 0.25 BTU-in / hr·sq.ft·°F, demonstrated a density of 0.830 lb / cu.ft, which is at least 7%, and specifically at least 9%, higher than the densities of Examples 1 and 2.
[0155] Even more surprisingly, Comparative Example 2 was formed with 14.3HT glass fibers (thereby considered "ultrafine fibers" as defined herein) and a binder composition including a polymeric polyol and a polycarboxylic acid monomer crosslinker. The product of Comparative Example 2, at a thickness of 5.5 inches and a k value of 0.23 BTU-in / (hr·ft 2 ·°F), demonstrated a density of 1.25 lb / ft 3 , at least 39% higher than the densities of Examples 1 and 2. TIFF2024522501000005.tif171153
[0156] Furthermore, at the same thickness and approximately the same R-value, Examples 1 and 2 increased material efficiency by more than 5 units compared to the products of Comparative Examples 1 and 2. These differences can be attributed at least to the increased areal weight required in Comparative Examples 1 and 2 to achieve k values comparable to those of Examples 1 and 2. Thus, as can be seen, the fibrous insulation products of the present invention can provide improved thermal performance at reduced areal weight, thereby improving the overall efficiency of the product.
[0157] The fiberglass insulation material of the present invention can have any combination or subcombination of the properties and ranges of properties disclosed herein. While the present invention has been illustrated by the description of its embodiments, it is not the intention of the applicant to limit or in any way restrict the scope of the invention as set forth in the claims to such details. Additional advantages and modifications will be readily apparent to those skilled in the art. While the fiber insulation product has been described herein as a flexible batt or blanket, other configurations and geometries can be used. Furthermore, the fiber insulation product can be used in a variety of ways, and such fiber insulation product is not limited to any particular application. Accordingly, the present invention in its broader aspects is not limited to the specific details, representative apparatus, and illustrated examples shown and described. Accordingly, departures from such details or modifications can be made without departing from the spirit and scope of the general inventive concept.
Claims
1. 1. An insulation product with improved material efficiency, comprising: A plurality of glass fibers; a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers; the glass fibers have an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm); The insulation product has a binder content (LOI) of 8% by weight or less; At densities (x) between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ), the insulation product has a thermal conductivity of 0.2 pcf / cm 3 , which satisfies the following formula (VII): Formula (VII) y = 40.1916068x 2 -120.5813540x+129.628397 The insulation product can achieve a material efficiency (y) expressed in R·ft 2 / lb that meets or exceeds a value (y) that satisfies:
2. The insulation product of claim 1 , wherein the insulation product has a density (x) of from 0.5 pcf (8.0 kg / m 3 ) to 1.35 pcf (21.6 kg / m 3 ).
3. 3. The insulation product of claim 1 or 2, wherein the insulation product has a material efficiency (y) of at least 55 R-ft2 / lb.
4. 2. The insulation product of claim 1, wherein the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness, and at least 30% by weight of the glass fibers are oriented within ±15° of a plane parallel to the length of the insulation product.
5. 10. The insulation product of claim 1, wherein prior to crosslinking, the formaldehyde-free binder composition comprises at least one monomeric polyol and polycarboxylic acid in a combined amount of at least 45 weight percent, based on the total weight of the binder composition.
6. At densities (x) between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ), the insulation product has a thermal conductivity of 0.2 pcf / cm 3 , which satisfies the following formula (VI): Formula (VI) y = 40.1916068x 2 -120.5813540x+131.7360668 2. The insulation product of claim 1, capable of achieving a material efficiency (y) expressed in R·ft 2 / lb that meets or exceeds a value (y) that satisfies:
7. A lightweight insulation product, comprising: a plurality of glass fibers having an average fiber diameter of less than 15HT (3.81 μm); a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers; the insulation product has an R-value ranging from 19 to 24, an areal weight (W) of 0.3 pounds per square foot (4.8 kg / m3) to 0.5 pounds per square foot (8.0 kg / m3), and a density of 0.7 pounds per cubic foot (11.2 kg / m3) to 1.0 pounds per cubic foot (16.0 kg / m3); The insulation product satisfies the following equation (2): Equation (2): ME = R value / W where ME is expressed in R-ft2 / lb and W is the product area weight in lbs / ft2, and ME is at least 28 R-ft2 / lb.
8. 8. The lightweight insulation product of claim 7, wherein the insulation product has a material efficiency of at least 50 R-ft2 / lb.
9. The insulation product has a thickness (T 1 9. The lightweight insulation product of claim 7 or 8, comprising:
10. 8. The lightweight insulation product of claim 7, wherein the insulation product achieves a thermal conductivity (k value) of 0.55 BTU-in / (hr-ft2-°F) or less.
11. 1. A method for improving material efficiency of an insulation product, the method comprising: fiberizing the molten glass into a plurality of glass fibers; coating the glass fibers with an aqueous formaldehyde-free binder composition; randomly depositing the glass fibers onto a moving conveyor to form an uncured glass fiber blanket; and passing the uncured fiberglass blanket through a curing oven to crosslink the binder composition and form the fibrous insulation product. The glass fibers have an average fiber diameter ranging from 8HT (2.03 μm) to 15HT (3.81 μm); the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness; at least 30 weight percent of the glass fibers in the insulation product are oriented within ±15° of a common plane defined by the length and width of the insulation product; At densities (x) between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ), the insulation product has a thermal conductivity of 0.2 pcf / cm 3 , which satisfies the following formula (VII): Formula (VII) y = 40.1916068x 2 -120.5813540x+129.628397 The method can achieve a material efficiency (y) expressed in R·ft 2 / lb that meets or exceeds a value (y) that satisfies:
12. The method of claim 11 , wherein the insulation product has a material efficiency (y) of at least 55 R·ft 2 / lb.
13. 13. The method of claim 11 or 12, wherein the insulation product has an areal weight (W) of between 0.3 pounds per square foot and 0.5 pounds per square foot.
14. At densities (x) between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ), the insulation product has a thermal conductivity of 0.2 pcf / cm 3 , which satisfies the following formula (VI): Formula (VI) y = 40.1916068x 2 -120.5813540x+131.7360668 12. The method of claim 11, wherein the method is capable of achieving a material efficiency (y) expressed in R·ft 2 / lb that meets or exceeds a value (y) that satisfies:
15. 1. An insulation product with improved material efficiency, comprising: A plurality of glass fibers; a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers; the glass fibers have an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm); The insulation product has a binder content (LOI) of 8% by weight or less; At densities (x) between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ), the insulation product has a thermal conductivity of 0.2 pcf / cm 3 , which satisfies the following formula (VI): Formula (VI) y = 40.1916068x 2 -120.5813540x+131.7360668 The insulation product can achieve a material efficiency (y) expressed in R·ft 2 / lb that meets or exceeds a value (y) that satisfies: